“It makes me feel like I have a place in this world.” An Interpretative Phenomenological Analysis Exploring Children’s Experiences of School Dogs Supporting their Wellbeing. - Smith, Kate (2024)
Research shows that there has been a concerning rise in reported mental health difficulties for children in the last decade (NHS Digital, 2022; Rider et al., 2021). Previous research has highlighted the potential benefits that animals can have on mental health and wellbeing in different settings e.g. care homes (Freedman et al., 2021), hospitals (Correale et al., 2022), universities (Lalonde et al., 2020), and schools (Beetz, 2013). With schools having an important role in supporting children’s mental health and wellbeing (Department for Education and Department of Health, 2015), it is worthwhile exploring the use of school dogs to support children’s wellbeing. Previous research exploring children’s views of school dogs supporting their wellbeing has, a) focused specifically upon children reading to dogs, and/or b) offers descriptive (surface-level) insight. Therefore, there is a gap in the literature as it does not offer an in-depth exploration of children’s views and experiences of a range of interactions with school dogs to support their wellbeing. This research study hopes to address this gap to offer a unique contribution to educational psychology research in this area.